Development of supplementary material using Wordwall for 12th-grade students in learning relative clauses - Yulius Patrick Darmawan; Made Hery Santosa; Kadek Sintya Dewi (Universitas Islam Malang, 2023)
The study aimed to develop supplementary material using Wordwall-based learning media for learning relative clauses and examined the experiences of 12th-grade students in using Wordwall. The study employed Design and Development (DnD) research method which conducted design, development, and evaluation steps. This study used the topic of the relative clause as a result of pre-observation in tackling an existing problem in learning relative clauses. This research used two instruments: a blueprint of supplementary material and a User Evaluation Questionnaire (UEQ). The UEQ examined 5 dimensions of users’ experiences in using a digital product: attractiveness, perspicuity, efficiency, dependability, stimulation, and novelty. The data were collected by analyzing the syllabus, preparing the Wordwall platform, distributing the questionnaire, and analyzing the questionnaire’s results. The questionnaire was filled with 32 students and 1 teacher who are taking English Language and Literature (Concentration) subjects. The data collected was analyzed and explained qualitatively and quantitatively. The results of the user experiences were attractiveness gained excellent (2.1), perspicuity gained above average (1.68), the efficiency gained excellent (1.88), dependability gained excellent (2.25), stimulation gained good quality (1.55), and novelty gained excellent quality (2.13). These results indicate that the developed supplementary material brings students attractive, fun, motivating, efficient, and fresh experiences in using Wordwall for learning relative clauses. Therefore, the developed Wordwall-based supplementary material for learning relative clauses material is very good to be implemented for the learning and teaching process for 12th-grade students.